The burden and predisposing factors of non-communicable diseases in Mashhad University of Medical Sciences personnel: a prospective 15-year organizational cohort study protocol and baseline assessment - Fariba Tohidinezhad; Ali Khorsand; Seyed Rasoul Zakavi; Reza Rezvani; Siamak Zarei-Ghanavati; Majid Abrishami; Ali Moradi; Mahmoud Tavakoli; Donya Farrokh; Masoud Pezeshki Rad; Bita Abbasi; Mitra Ahadi; et al. (BMC, 2020)
Abstract Background The rising burden of premature mortality for Non-Communicable Diseases (NCDs) in developing countries necessitates the institutionalization of a comprehensive surveillance framework to track trends and provide evidence to design, implement, and evaluate preventive strategies. This study aims to conduct an organization-based prospective cohort study on the NCDs and NCD-related secondary outcomes in adult personnel of the Mashhad University of Medical Sciences (MUMS) as main target population. Methods This study was designed to recruit 12,000 adults aged between 30 and 70 years for 15 years. Baseline assessment includes a wide range of established NCD risk factors obtaining by face-to-face interview or examination. The questionnaires consist of demographic and socioeconomic characteristics, lifestyle pattern, fuel consumption and pesticide exposures, occupational history and hazards, personal and familial medical history, medication profile, oral hygiene, reproduction history, dietary intake, and psychological conditions. Examinations include body size and composition test, abdominopelvic and thyroid ultrasonography, orthopedic evaluation, pulse wave velocity test, electrocardiography, blood pressure measurement, smell-taste evaluation, spirometry, mammography, and preferred tea temperature assessment. Routine biochemical, cell count, and fecal occult blood tests are also performed, and the biological samples (i.e., blood, urine, hair, and nail) are stored in preserving temperature. Annual telephone interviews and repeated examinations at 5-year intervals are planned to update information on health status and its determinants. Results A total of 5287 individuals (mean age of 43.9 ± 7.6 and 45.9% male) were included in the study thus far. About 18.5% were nurses and midwives and 44.2% had at least bachelor's degree. Fatty liver (15.4%), thyroid disorders (11.2%), hypertension (8.8%), and diabetes (4.9%) were the most prevalent NCDs. A large proportion of the population had some degree of anxiety (64.2%). Low physical activity (13 ± 22.4 min per day), high calorie intake (3079 ± 1252), and poor pulse-wave velocity (7.2 ± 1.6 m/s) highlight the need for strategies to improve lifestyle behaviors. Conclusion The PERSIAN Organizational Cohort study in Mashhad University of Medical Sciences is the first organizational cohort study in a metropolitan city of Iran aiming to provide a large data repository on the prevalence and risk factors of the NCDs in a developing country for future national and international research cooperation.